How external load of youth basketball players varies according to playing position, game period and playing time - Reina, M.; García-Rubio, J.; Esteves, P. T.; Ibáñez, S. J. (International Journal of Performance Analysis in Sport, 2020)
One of the main challenges in sports coaching is to monitor competitive performance in order to adjust training load. The purpose of this study was to evaluate how playing position, game period and playing time influenced the physical demands of youth basketball players. Six measures of external load (total distance covered, high-speed distance, number of accelerations, decelerations, jumps and player load) were collected from 48 youth basketball players, over the course of a short tournament, through the use of a local positioning tracking system (WIMUPROTM). Player activity profiles were analysed in function of i) player position (guard, forward and centers), ii) game period (Q1, Q2, Q3, Q4) and iii) playing time (important players vs less important players). Forwards presented a greater level of variability in the external load measures while guards were the most stable players throughout the game. An increase in the level of variability of players` workloads was observed during the game, especially from periods Q1 to Q3 and Q3 to Q4. The number of jumps per minute emerged as the variable with greater variation in association with playing time. Our results provide further support for the importance of considering performance variability for the design of individual training loads.